Singing the Lord's song in a strange land : hymnody in the history of North American Protestantism - Blumhofer, Edith Waldvogel; Noll, Mark A., 1946- (Religion and American culture (Tuscaloosa, Ala.), 2004)
The latest scholarship on the role of hymns in American evangelicalism. Music and song are important parts of worship, and hymns have long played a central role in Protestant cultural history. This book explores the ways in which Protestants have used and continue to use hymns to clarify their identity and define their relationship with America and to Christianity. Representing seven groups--Baptists, Presbyterians, Lutherans, Mennonites, Holiness, Hispanics, and Evangelicals--the nine essays reveal how hymns have helped immigrants to establish new identities, contributed to the body of worshi.